2017
DOI: 10.1038/srep40548
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of corneal epithelial cell-derived exosomes in corneal wound healing and neovascularization

Abstract: Specific factors from the corneal epithelium underlying the stimulation of stromal fibrosis and myofibroblast formation in corneal wound healing have not been fully elucidated. Given that exosomes are known to transfer bioactive molecules among cells and play crucial roles in wound healing, angiogenesis, and cancer, we hypothesized that corneal epithelial cell-derived exosomes may gain access to the underlying stromal fibroblasts upon disruption of the epithelial basement membrane and that they induce signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 33 publications
4
106
0
Order By: Relevance
“…We have previously demonstrated that EVs can be isolated from cultured corneal epithelial and stromal cells and identified by TEM (Han et al, ). To examine if the secretion of EVs can be visualized in a 3D in vivo ‐like culture, HCFs were cultivated in a VitC‐rich medium that stimulates extracellular matrix secretion and assembly.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously demonstrated that EVs can be isolated from cultured corneal epithelial and stromal cells and identified by TEM (Han et al, ). To examine if the secretion of EVs can be visualized in a 3D in vivo ‐like culture, HCFs were cultivated in a VitC‐rich medium that stimulates extracellular matrix secretion and assembly.…”
Section: Resultsmentioning
confidence: 99%
“…To show that EVs are involved in signaling for corneal wound healing, we first needed to prove that EVs were present in the cornea. This was accomplished by Han et al (), who showed that EVs could be isolated from both human epithelial and stromal cells in culture. In the present study, we took the next step and examined if EVs could be observed in a more natural 3D environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jangamreddy et al found that one kind of peptide analogs as alternatives to collagen promoted regeneration of corneal tissue by stimulating in-growing corneal epithelium cells to secrete EVs for generating matrix components [55]. During corneal wound healing, mouse corneal epithelial cell-derived exosomes induced fibroblast proliferation and transformation of keratocytes to myofibroblasts, mediating intercellular communication between the corneal epithelium and stroma [56]. Besides, exosomes derived from normal human corneal limbal keratocytes were found to greatly enhance proliferation and wound healing rates of primary limbal epithelial cells, likely via activating Akt signaling [57].…”
Section: Corneal Allograft Rejectionmentioning
confidence: 99%